2018
DOI: 10.1116/1.5063750
|View full text |Cite
|
Sign up to set email alerts
|

Multitechnique investigation into the aqueous behavior of plasma polymers

Abstract: Plasma polymers are often used in applications requiring aqueous immersion; therefore, it is important to understand how this exposure affects the physical and chemical properties of the films. Three different plasma polymer films were deposited at different distances from the electrode, and the film properties were characterized using contact angle, ellipsometry, and x-ray photoelectron spectroscopy. The film behaviors in aqueous solutions were studied via quartz crystal microbalance with dissipation (QCM-D).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The decreases in film thickness and increases in the COOH/R groups as the distance from the electrode increases are likely to be contributed to by reduced monomer fragmentation further from the electrode. Our previous research has shown decreasing electron flux with increasing distances from the electrode [3], results in decreased electron collisions [34]. A previous study has shown that the optical emission of an ethylene plasma peaks 10–15 mm from the electrode and decreases as the distance from the electrode increases, indicating decreasing plasma density and therefore lower collisions further from the electrode [35].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The decreases in film thickness and increases in the COOH/R groups as the distance from the electrode increases are likely to be contributed to by reduced monomer fragmentation further from the electrode. Our previous research has shown decreasing electron flux with increasing distances from the electrode [3], results in decreased electron collisions [34]. A previous study has shown that the optical emission of an ethylene plasma peaks 10–15 mm from the electrode and decreases as the distance from the electrode increases, indicating decreasing plasma density and therefore lower collisions further from the electrode [35].…”
Section: Resultsmentioning
confidence: 99%
“…Plasma polymerization was undertaken at low pressure with a stainless steel T-piece reactor with a volume of 16.2 L and 170 mm diameter internal aluminium disk electrode, as previously described [3]. Briefly, the electrode was connected to a 13.56 MHz radio frequency (RF) power source generator (Coaxial Power Ltd., Eastbourne, UK) with an impedance-matching network to generate the plasma.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations